POTENSI PENGGUNAAN ACEPROMAZINE SEBAGAI SEDIAAN TRANSQUILIZER PADA TRANSPORTASI IKAN PATIN - Andriyanto '; A Sutisna; W Manalu; L Andini; R Hidayat; K Suanda; S Valinata (Berkala Perikanan Terubuk, 2010)
This study was designed to assess the potential of acepromazine (ACP) asa transquilizer in catfish (Pangasius pangasius) during transportation withdifferent timed of administration (morning and afternoon). This research wasconducted by using method of dipping the fish into water mixed withacepromazine. Fish tha used for the study were 3 weeks old catfish, which have 5cm-body length and the body weight around 6 grams. Six hundred catfish weredivided into a completely randomized design with a 2x6 factorial arrangement.The first factor was dipping time that consisted of two levels, morning andafternoon. The second factor was dosage of acepromazine that consisted of sixlevels, 0 ppm, 5 ppm, 15 ppm, 25 ppm, 35 ppm, and 45 ppm. The result showedthat the effective dose of acepromazine being used in catfish was 25 ppm with adipping time in the morning. The onset of this dosage was 96.55 minutes, theduration length was 81.76 minutes, and the mortality rate was equal to 10%.